2007
DOI: 10.1161/01.res.0000257912.78915.af
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Impairment of Endothelial Progenitor Cells Is Corrected by Growth Hormone Mediated Increase of Insulin-Like Growth Factor-1

Abstract: Abstract-Aging is associated with an increased risk for atherosclerosis. A possible cause is low numbers and dysfunction of endothelial progenitor cells (EPC) which insufficiently repair damaged vascular walls. We hypothesized that decreased levels of insulin-like growth factor-1 (IGF-1) during age contribute to dysfunctional EPC. We measured the effect of growth hormone (GH), which increases endogenous IGF-1 levels, on EPC in mice and human subjects. We compared EPC number and function in healthy middle-aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
206
2
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(232 citation statements)
references
References 54 publications
18
206
2
6
Order By: Relevance
“…Circulating endothelial progenitor cells (EPCs) can modulate the repair and regeneration of the endothelium associated with vascular ageing, atherosclerosis and CAD. It has been reported that elderly healthy subjects had lower circulating EPCs with impaired function and increased senescence when compared to young people 25. Circulating EPCs obtained from CAD patients, compared with from age‐matched healthy subjects, showed shorter telomere length and lower telomerase activity 26.…”
Section: Discussionmentioning
confidence: 96%
“…Circulating endothelial progenitor cells (EPCs) can modulate the repair and regeneration of the endothelium associated with vascular ageing, atherosclerosis and CAD. It has been reported that elderly healthy subjects had lower circulating EPCs with impaired function and increased senescence when compared to young people 25. Circulating EPCs obtained from CAD patients, compared with from age‐matched healthy subjects, showed shorter telomere length and lower telomerase activity 26.…”
Section: Discussionmentioning
confidence: 96%
“…During progression of prostate cancer, local levels of both IGF-1 and its receptor (IGF-1R) increase (Kaplan et al, 1999). Like many growth factors, IGF-1 has the potential to reverse the age-associated decline in endothelial cell function (Thum et al, 2007). Moreover, IGF-1 upregulates the expression of modulators of endothelial cell function such as VEGF, MT1-MMP, and MMP2; this regulation requires signalling through the IGF-1 receptor via both the PI3 kinase and MAP kinase pathways (Miele et al, 2000;Grzmil et al, 2004;Zhang et al, 2004).…”
Section: Growth Factorsmentioning
confidence: 99%
“…One of the major concerns when envisioning autologous (progenitor/stem) cell therapy in cardiovascular medicine, is the presumed dysfunctional progenitor cell phenotype in older and diseased patients burdened with risk factors, as evidenced for early outgrowth EPCs of monocytic origin (also known as circulating angiogenic cells),9, 10, 11, 12 CD133 + /VEGFR2+ circulating EPCs,10, 13 colony‐forming‐unit EPCs (CFU‐Hill),13, 14 bone‐marrow–derived mononuclear cells (MNCs)15 and hematopoietic stem cells 11…”
Section: Introductionmentioning
confidence: 99%